Acceptance of Electronic Payments : A case study of the Restaurant Association in Trang Province - รักไทย, ธีรเดช (Journal of Energy and Environment Technology of Graduate School Siam Technology College, 2019)
The purpose of this study was to study the factors influencing acceptance of electronic payment literature review and literature synthesis. The entrepreneurs have not decided to use the electronic payment system, the main reasons are: 1) lock of understanding of electronic payments 2) lack of confidence in the security of the system 3 there is no modern equipment sufficient to operate and 4) lack of new generation personnel in the caretaker facility. These are the basic factors that will lead to a smoothed-up research process using case studies. Trang restaurant operator in the future.